2018
DOI: 10.1111/iju.13528
|View full text |Cite
|
Sign up to set email alerts
|

Uridine 5'diphospho‐glucuronosyltransferase 1A expression as an independent prognosticator in urothelial carcinoma of the upper urinary tract

Abstract: These results suggest a preventive role of uridine 5'diphospho-glucuronosyltransferase 1A signals in the development and progression of upper urinary tract urothelial carcinoma. Loss of uridine 5'diphospho-glucuronosyltransferase 1A expression might serve as an independent predictor of poor prognosis in patients with upper urinary tract urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…In SVHUC cells subsequently exposed to MCA, GATA3 knockdown resulted in the promotion of neoplastic transformation, along with down-regulation of the expression of tumor suppressor genes (e.g., p53, p21, PTEN) and up-regulation of that of oncogenes (e.g., c-myc, cyclins, FGFR3) [33], suggesting its function as a suppressor of urothelial tumor. Immunohistochemical studies in bladder [65] or UUT [62] specimens further showed significant down-regulation of UGT1A expression in tumors, compared with non-neoplastic urothelial tissues.…”
Section: Gata3mentioning
confidence: 94%
See 1 more Smart Citation
“…In SVHUC cells subsequently exposed to MCA, GATA3 knockdown resulted in the promotion of neoplastic transformation, along with down-regulation of the expression of tumor suppressor genes (e.g., p53, p21, PTEN) and up-regulation of that of oncogenes (e.g., c-myc, cyclins, FGFR3) [33], suggesting its function as a suppressor of urothelial tumor. Immunohistochemical studies in bladder [65] or UUT [62] specimens further showed significant down-regulation of UGT1A expression in tumors, compared with non-neoplastic urothelial tissues.…”
Section: Gata3mentioning
confidence: 94%
“…Correspondingly to a potential difference in the susceptibility to bladder carcinogens between men and women, the expression levels of mouse Ugt1a subtypes were shown to be considerably higher in the bladders from females than in those from males [60]. In immunohistochemical studies in bladder [61] or UUT [62] specimens, UGT1A expression was down-regulated in tumors, compared with non-neoplastic urothelial tissues, as well as in high-grade and/or muscle-invasive tumors, compared with low-grade and/or non-muscle-invasive tumors, and its positivity was associated with better patient outcomes.…”
Section: Udp-glucuronosyltransferases (Ugts)mentioning
confidence: 97%
“…In addition, UGT1A expression was positively and negatively correlated with the levels of ERα and ERβ, respectively, but not those of AR. In a recent immunohistochemical study in UUT urothelial carcinoma tissues, the expression of UGT1A was down-regulated in tumors, compared with non-neoplastic urothelial tissues, and in MI tumors, compared with NMI tumors ( 119 ). Furthermore, UGT1A positivity in M0 tumors was found to be an independent predictor for better cancer-specific survival (HR=0.28; P=0.018).…”
Section: Molecules Whose Expression Is Modulated Via Steroid Hormone Receptor Signalsmentioning
confidence: 95%
“…89 It is an important enzyme of glucuronidation (detoxification mechanism of the body), responsible for the biotransformation of carcinogens that enter into the body through diet or as pollutants from the air. 90 In the bladder, acidic urine is responsible for the hydrolysis of glucuronide-carcinogen to release ultimate carcinogens. 91, 92 QR plays a pivotal role in the detoxification process by reducing electrophilic quinones.…”
Section: Anticarcinogenic Mechanism Of Essential Oilmentioning
confidence: 99%